Emerging trends and risk factors for perianal surgery in Crohn's disease: a 20-year national population-based cohort study. Issue 8 (August 2016) - Chhaya, Vivek; Saxena, Sonia; Cecil, Elizabeth; Subramanian, Venkataraman; Curcin, Vasa; Majeed, Azeem; Pollok, Richard C.
Abstract : Background: Little is known about the rates of perianal surgery (PAS) in Crohn's disease (CD). Our aim was to determine trends in PAS, the timing of surgery relative to the diagnosis of CD and to identify subgroups at risk of PAS. Materials and methods: We identified 9391 incident cases of CD between 1989 and 2009. We defined three eras: era 1 (1989–1995), era 2 (1996–2002) and era 3 (2003–2009), and determined trends in procedure type and the time to first PAS relative to the date of diagnosis. We used Kaplan–Meier analysis to calculate the rate of first PAS and performed Cox regression to determine subgroups at risk of PAS. Results: Among the 9391 incident cases of CD, 405 (4.3%) underwent PAS. The overall rate of PAS was 5.5% [95% confidence interval (CI): 4.9–6.2%] 10 years after diagnosis. 34% ( n =137) of all patients undergoing PAS had surgery in the 5 years before CD diagnosis. Abscess drainage increased from 34 to 58%, whereas proctectomy decreased from 16 to 6% between eras 1 and 3, respectively. Men [hazard rate (HR) 1.51, 95% CI: 1.24–1.84], those aged 17–40 years (HR 1.69, 95% CI: 1.09–2.02 vs. those aged >40 years) and those with a history of previous intestinal resection (HR 28.5, 95% CI: 22.2–36.5) were more likely to have PAS. Conclusion: Around one-third of patients have a PAS in the 5 years preceding their diagnosis of CD. Surgical practice has changed over 20 years, with a decrease in proctectomy and a concurrent increase in abscess drainage that is likely to reflect improvements in therapeutic practice.